Oxidative Stress Biomarkers in the Equine Erythrocytes After In Vitro Treated with Leaf Extract Obtained from Thymus × Porcii Borbás (Lamiaceae) - Honcharenko, Vitaliy; Tkachenko, Halyna; Prokopiv, Andriy; Nachychko, Viktor; Kurhaluk, Natalia; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Antioxidants from natural products are important to protect against free radicals. The literature has documented the antioxidant activity of the Thymus genus (Lamiaceae) in inhibiting the formation of free radicals generation. In line with our previous study, we continue to assess the antioxidant potential of four species and one interspecific hybrid of Thymus genus sampled in the western part of Ukraine on equine erythrocytes’ model. Therefore, in the present study, the oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS), carbonyl derivatives content of protein oxidative modification, total antioxidant capacity (TAC)], as well as HCl-induced hemolysis in the equine erythrocytes, was used for assessing the antioxidant activity of extract obtained from the leaves of Th. × porcii Borbás (a hybrid between Th. pannonicus and Th. pulegioides). Leaves of Th. × porcii were sampled in the grass stand, on the side of the footpath of the race track (Medovoi Pechery Str., Lviv, Ukraine; N 49˚49’15.1", E 24˚05’12.5", 348 m a.s.l.). Equine erythrocytes aliquots were used in the study. For positive control (blank), phosphate buffer was used. After incubation of the mixture at 37 °C for 60 min with continuous stirring, samples were used for the biochemical assays. The aldehydic and ketonic derivatives level, as well as total antioxidant capacity, was non-significantly altered after in vitro incubation with an extract obtained from leaves of Th. x porcii. The Th. x porcii extract caused to increase of TBARS content as a biomarker of lipid peroxidation in the extract-treated erythrocytes, and these results were statistically significant. Total antioxidant capacity was non-significantly increased. When Th. x porcii extract (5 mg/mL) was added to the erythrocyte suspension, the maximum level of hemolysis occurred after 8.5 min of incubation with 0,1M HCl (17.91 ±1.87 %). The total duration of hemolysis after Th. x porcii extract (5 mg/mL) incubation was 11.5 min. Our results showed that HCl-induced hemolysis in a typical time-dependent manner. the extract obtained from leaves of Th. x porcii (5 mg/mL) has a mild cytotoxic activity on the equine erythrocytes increasing the level of lipid peroxidation biomarker and hemolysis rate. Investigation of the mechanism of action revealed that this extract has hemolytic activity. Therefore, Th. x porcii extract at a concentration of 5 mg/mL induced the increase of hemolyzed erythrocytes and caused to decrease in hemolysis duration. Screening of Thymus species for other biological activities including antioxidant activities is essential and may be effective for searching the preventive agents in the pathogenesis of some metabolic diseases.